Paleodiet and niche breadth in Middle Miocene rodents and ungulates from northern South America revealed through stable isotope analyses - Laura E. Arias-Concha; Michael J. Ziegler; Patrick Roberts; Francisco J. Urrea-Barreto; Darin Croft; Siobhán B. Cooke; Catalina Zorro; Jana Ilgner; Erin Scott; Andres Vanegas-Vanegas; Cesar Augusto Perdomo; Andrés Link (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Trophic niche structure of a sea urchin assemblage in southeastern Brazil - Carlos Alberto da Silva Junior; Renato Hajenius Aché de Freitas; Pedro Vianna Gatts; Carlos Eduardo de Rezende; Cesar Augusto Marcelino Mendes Cordeiro (Continental Shelf Research, 2026)

The Brazilian soil total available water (TAW) acquired by remote sensing and machine learning techniques - Letícia Guadagnin Vogel; Fellipe Alcantara de Oliveira Mello; José Alexandre Melo Demattê; Quirijn de Jong van Lier; Jorge Tadeu Fim Rosas; Leonardo Inforsato; Merilyn Taynara Accorsi Amorim; Nícolas Augusto Rosin; Michele Duarte de Menezes; Marcelo Henrique Procópio Pelegrino; Danilo Cesar de Mello; Renan Falcioni (CATENA, 2026)

Biological nitrogen fixation by Prosopis juliflora (Sw.) DC stands in the Brazilian semi-arid region - Edilandia Farias Dantas; Everardo Valadares de Sá Barretto Sampaio; Jéssica Rafaella de Sousa Oliveira; Augusto Cesar de Arruda Santana; Alesson Gabriel Xavier da Hora; Leandro Reis Costa Santos; Juscélia da Silva Ferreira; Plínio Barbosa de Camargo; Ana Dolores Santiago de Freitas (Agroforestry Systems, 2026)
Prosopis juliflora was introduced to the Brazilian semi-arid region as a forage and firewood plant and spontaneously dispersed to valley areas and now forms almost pure stands in more than 500,000 ha of the region. Since eradication is not being considered, studies on the advantages and disadvantages are necessary. One of the potential advantages is the capability of symbiotically fixing atmospheric N 2 . We determined P. juliflora N fixation in six valley areas of Pernambuco state, Brazil. In each area, leaf and wood biomasses were estimated, N concentrations and amounts determined and N fixation in leaves estimated by the 15 N technique. Aboveground and leaf biomasses averaged 44.1 Mg ha −1 , and 2.1 Mg ha −1 , respectively. The nitrogen derived from the atmosphere (%Ndfa) in the leaves averaged 38.8%, corresponding to 24.2 kg ha −1 yr −1 of N fixation. An indirect rough estimation of the average N stock derived from fixation in the woody parts was based on the assumption that the 15 N values in the leaves and wood in the same plant was equal, and amounted to 74.1 kg ha −1 Considering the fixed N in the leaves as a stock, adding the estimated N stock in the wood, and extrapolating for the 113 thousand hectares covered by P. juliflora in Pernambuco, Paraíba and Rio Grande do Norte states would be equivalent to a stock of 11.1 Gg of N. Despite being a crude estimate, it indicates that P. juliflora can potentially contribute to a significant amount of fixed N in the plant-soil system in the Brazilian Northeast region.

Laboratory-based assessment of polycyclic aromatic hydrocarbon uptake in a Southwestern Atlantic endemic coral - Gislaine Vanessa de Lima; Marina Cunha Passarelli-Loura; Carolina Gonçalves de Lima; Gabriel Mendes Izar; Ana Cecília Rizzatti de Albergaria-Barbosa; Natália Menezes; Yasmim Caroline Anunciação Gomes; Luis Guilherme França Côrtes da Silva; Natanael Cícero Cavalcanti Bezerra; Cláudio Henrique Gomes Fialho; José Renato Mendes de Barros Correia; Gisele Olímpio da Rocha; et al. (Marine Pollution Bulletin, 2026)

Molecular architectures of self-assembling peptides for combating resistant bacteria - Cesar Augusto Roque-Borda; Waleska Stephanie da Cruz Nizer; Subham Kumar Vishwakarma; Oswaldo Julio Ramirez Delgado; Zidane Qriouet; Andréia B. Meneguin; Fernando Rogério Pavan (Chemical Engineering Journal, 2026)

Multi-stranded intraplate shear zone revealed by combined morphostructural and ERT imaging: Insights from the Serrote fault system, Brazil - Saul Hartmann Riffelᵃ; Viviane Barbosa Gimenezᵇ; Cesar Augusto Moreiraᵃ; Norberto Moralesᵃ; Iata Anderson de Souzaᵃ; Daniela Kuranakaᵃ (Tectonophysics, 2026)

Supplementation of the antimicrobial peptide Ctx(Ile21)-Ha microcapsules improves fecal recovery dynamics in suckling piglets without altering pre-weaning growth - Hanyeny Raiely Leite Silva; Sophia Silva Carrijo; Cesar Augusto Roque-Borda; Mariane De Freitas Genari Severino; Wendell Queiroz Leite; Ligia Cardoso dos Santos; Larissa Freire Mariano; Leonardo Alexander de Oliveira Campos; Thais Cristina dos Anjos Sevilhano; Marcelo Gindri; Priscilla Ayleen Bustos Mac-Lean Megna; Eduardo Festozo Vicente (Livestock Science, 2026)

Performance of Gold Tailings Stabilized with a One-Part Alkali-Activated Binder - Victor Núñez; Andres Lotero; Cezar Augusto Bastos; Nilo Cesar Consoli (Geotechnical and Geological Engineering, 2026)
Dry stacking has emerged as a safer alternative to conventional tailings dams for gold tailings (GT) disposal. Despite growing interest in mine tailings stabilization, much research has focused on conventional binders or alkali-activated binders (AABs) using the two-part method. However, studies on one-part AABs for filtered GT in dry stacking applications remain scarce. This study evaluates the unconfined compressive strength (q u ), secant modulus of elasticity (E 50 ), durability, and microstructural characteristics of GT stabilized with a one-part AAB composed of GGBS, sodium hydroxide, and sodium silicate, comparing its performance with ordinary Portland cement (OPC). The AAB-stabilized GT achieved a maximum q u of 9.18 MPa, approximately 33% higher than that of OPC-stabilized GT (6.92 MPa). Rapid strength development was observed, with 93% of the 63-day strength reached after only 7 days of curing (8.55 MPa). The maximum E 50 reached 2051.7 MPa, nearly 1.9 times greater than that obtained with OPC. Statistical analyses identified binder content and degree of compaction as the primary factors controlling strength and stiffness. Regression models and a porosity/binder content index were proposed as a rational methodology for predicting mechanical behavior and supporting binder mix design. The best-performing AAB mixture exhibited lower mass loss of 1.39%, indicating not only high mechanical performance but also excellent durability. Microstructural analyses qualitatively revealed denser matrices and the formation of hybrid C(N)-A-S-H gels in AAB-stabilized GT, explaining its enhanced performance. In contrast, OPC-stabilized GT exhibited more porous matrices containing C-(A)-S-H gels and ettringite. These findings demonstrate the potential of one-part AAB as a high-performance alternative to OPC for the stabilization of GT in dry stacking.

Where the Black-Horned Capuchins Roam: Present and Future Ranges of Sapajus nigritus and Their Overlap with Pine Plantations - Luiz Carlos Lopes da Silveira; Amanda Köche Marcon; Dieter Liebsch; Cesar Augusto Marchioro (Ecosystems, 2026)
The introduction of pines in Southern America to supply the wood industry has promoted interactions with native fauna, including the black-horned capuchin ( Sapajus nigritus [Goldfuss, 1809]). In southern Brazil, this species feeds on pine sap, causing significant economic losses. We used the maximum entropy algorithm (MaxEnt) to model the current and future potential distribution of S. nigritus under different climate change scenarios and conducted spatial analyses to evaluate land cover changes and the overlap between pine-producing areas and the species’ range. Current climatic suitable conditions cover about 1 million km 2 , mainly in southern and southeastern Brazil, but projected to decline by 31.7 to 89.8% depending on climate change scenario and timeframe. Presently, the distribution of S. nigritus overlaps with 96.7% of pine-producing municipalities and 86.5% of Brazil’s pine plantation area. Over the past 38 years, tree plantations expanded markedly within the species’ range, increasing from 1.1% in 1985 to 4.5% in 2023. During the same period, the number of native forest and plantation fragments grew by 35.1% and 569.3%, respectively, while their average size declined 25.6% and 37.0%. These changes indicate severe habitat fragmentation and isolation. Historical land use trends have likely intensified interactions between capuchins and commercial pine plantations, explaining the increase in reported damage. Our findings underscore the pressing need for integrated management strategies that balance economic interests in forestry with the conservation of S. nigritus amid accelerating environmental change.

Advances in recombinant protein bioprocessing: integrating technological innovation and environmental sustainability - Milena de Freitas Trindade Mota; Luis Gustavo Carvalho Pacheco; Cesar Augusto Piedrahita Aguirre; Elaine Christine de Magalhães Cabral Albuquerque (Biotechnology Letters, 2026)
This study aims to provide an integrated assessment of recombinant protein bioprocessing by combining technological maturity frameworks (TRL/BRL) with environmental sustainability indicators. A structured literature-based analysis was conducted, covering recent advances in bioprocess engineering, including precision fermentation, artificial intelligence-assisted control, and sustainability assessment tools such as life cycle analysis (LCA) and process mass intensity (PMI). Recombinant protein production using microbial systems, such as Escherichia coli, demonstrates high scalability and cost-efficiency, with reported emissions significantly lower than those of conventional pharmaceutical synthesis (≈ 20 vs 351 kg CO 2 eq/kg product). However, critical gaps persist between laboratory-scale innovation and industrial implementation, particularly in emerging economies. The integration of digital tools, including AI and digital twins, shows strong potential to improve process optimization and scale-up success rates. Bridging the gap between technological development and industrial deployment requires integrating process design, sustainability metrics, and readiness frameworks. Targeted innovation strategies are essential to accelerate biopharmaceutical development and enhance global health outcomes.

Replacing corn silage with cactus cladodes, sugarcane bagasse, and urea reduces nitrogen efficiency and microbial protein synthesis in sheep - Caio Cesar Carneiro dos Santos; Kaique Renan da Silva Salvador; Ana Clara Silva Pinheiro Leite; Melissa Silva Paiva; Michelle Christina Bernardo de Siqueira; Antônio Jorge Corrêa de Araújo; Gilmar Natanael de Souza; José Augusto Bastos Afonso da Silva; Francisco Fernando Ramos de Carvalho; João Paulo Ismério dos Santos Monnerat; Marcelo de Andrade Ferreira (Small Ruminant Research, 2026)

Pregnancy outcomes after TAI with cooled versus frozen bovine semen: A meta-analysis - César Augusto Pinzón-Osorio; Dionet Keny Bellido-Quispe; Verônica Rafaela Benvenutti; Cesar Augusto Camacho-Rozo; Oluwagbemiga Ademola Dada; Marcelo Bertolini (Animal Reproduction Science, 2026)

Comparing mesenchymal stem/stromal cells from dermis discarded in elective surgeries: Identifying optimal sources for regenerative medicine - Helena Debiazi Zomer; Adriane Cristina Fagundes; Lais Andrade Ferreira; Augusto Cesar Spadaccia Asciutti; Priscilla Barros-Delben; Maiara Marques da Silva; Julia Mitze; Talita da Silva Jeremias; Andrea Gonçalves Trentin (Tissue and Cell, 2026)

Mercury in southern legal Amazonia: evaluating Prochilodus nigricans (Agassiz, 1829) as a bioindicator species and the risk of its consumption - Augusto Cesar da Costa Castilho; Kleber Solera; Vinícius José Santos Lopes; Gleyce Alves Machado; Ricardo Lopes Tortorela de Andrade; Leandro Dênis Battirola (Environmental Monitoring and Assessment, 2026)
Mercury (Hg), a highly toxic metal, continues to be widely used in artisanal and small-scale gold mining (ASGM), particularly in the Amazon region. Its improper use and disposal contribute to the contamination of aquatic ecosystems, impacting fish and the human populations that rely on them for food. This study evaluated mercury contamination, measuring total mercury (THg) in the Peixoto de Azevedo River Basin, located in the southern Brazilian Legal Amazon, by analyzing scale, skin, muscle, and liver tissues of Prochilodus nigricans , a key species in the local diet. Mercury was detected in all tissues and across all river stretches, with higher levels observed near mining sites, suggesting the association between ASGM and environmental contamination. The liver showed the highest THg levels (1.581 mg kg⁻ 1 ), followed by scales (0.537 mg kg⁻ 1 ), skin (0.153 mg kg⁻ 1 ), and muscle (0.087 mg kg⁻ 1 ). The results obtained for scales indicate their potential as a bioindicator matrix, allowing the use of less invasive sampling approaches for the species. Although muscle THg levels were below the FAO legal threshold (0.5 mg kg⁻ 1 ), the estimated health risk (THQ > 1) suggests potential harm to riverine populations due to high fish consumption. These findings underscore the urgent need for continuous monitoring and effective mitigation strategies to protect both aquatic ecosystems and public health in ASGM-affected regions.

Everyday storage and handling of PET bottled water increase human exposure to nano- and microplastics: Influence of socio-economic factors - Kazi Albab Hussain; Haoyu Dong; Alex Tamayo-Aguilar; Seulki Kim; Cesar Augusto Gomez Pena; Silvia Foss; Lucia Fernandez-Ballester; Yongfeng Lu; Yusong Li (Water Research, 2026)

Soluble and insoluble fiber blend improves farrowing performance and colostral immunoglobulin concentration in sows without altering fecal microbiota - Bruno Bracco Donatelli Muro; Rafaella Fernandes Carnevale; Matheus Saliba Monteiro; Diego Feitosa Leal; André Pegoraro Poor; Francisco Alves Pereira; Vera Letticie de Azevedo Ruiz; Cesar Augusto Pospissil Garbossa (The Veterinary Journal, 2026)

Global Suitable Habitats for Spodoptera litura and the Implications for Brazilian Agriculture - Luiz Carlos Lopes da Silveira; Cesar Augusto Marchioro (Neotropical Entomology, 2026)
Invasive alien species can significantly impact the environment, public health, and food production. Identifying high-risk areas is essential for implementing preventive measures, especially for species with several traits linked to invasive behavior, such as Spodoptera litura (F.). This study aimed to predict the potential global distribution of S. litura and assess its implications for five major crops in Brazil. Climatic suitability was estimated using the MaxEnt correlative algorithm, with fifty models generated by varying feature classes and regularization multiplier values. The best model selected based on the corrected Akaike Information Criterion demonstrated strong predictive performance, with high Area Under the Curve (AUC train = 0.92, AUC test = 0.86) and Continuous Boyce Index (CBI train = 0.95, CBI test = 0.75) values. Predictions identified highly and moderately suitable areas for S. litura across all continents, including regions where the species has not yet been recorded, such as the Neotropics. In Brazil, highly suitable areas include the mid-west, northeastern coast, and the southeastern and southern regions. Among the assessed crops, citrus (97.2%) had the greatest overlap with the suitable range for S. litura , followed by rice (94.2%), coffee (90.3%), and soybean (72.8%). These findings suggest that S. litura could cause significant economic damage if introduced and spread in Brazil. The results of this study can inform the development of preventive measures against the introduction and spread of this important agricultural pest, especially on high-risk areas near airports and seaports with intense international trade and in proximity to host crops.

Probiotics and enzymes in weaned piglets’ diets can lower belly nosing frequency and improve performance and nitrogen balance - Bruno Braga Carnino; Ana Ligia Braga Mezzina; Nadia de Almeida Ciriaco Gomes; Guilherme Cunha Gottschall; Bruno Bracco Donatelli Muro; Leticia Gomes de Morais Amaral; Cesar Augusto Pospissil Garbossa; Vinícius de Souza Cantarelli (Tropical Animal Health and Production, 2026)

Neutral detergent fiber as a limiting factor in replacing corn silage with cactus cladodes (Opuntia stricta (Haw.) Haw) plus sugarcane bagasse and urea - Caio Cesar Carneiro dos Santos; Darlan Silva dos Santos; Kaique Renan da Silva Salvador; Yasmin dos Santos Silva; Silas Boaventura Felix; Thayane Vitória Monteiro Santos; Milena Nóbrega Rabelo; Michelle Christina Bernardo de Siqueira; José Augusto Bastos Afonso da Silva; Francisco Fernando Ramos de Carvalho; João Paulo Ismério dos Santos Monnerat; Marcelo de Andrade Ferreira (Small Ruminant Research, 2026)

Economic perspective of expanded space allowance for group-housed gestating sows: Aligning profitability and welfare compliance - Laya Kannan Silva Alves; Camila Raineri; Monique Danielle Pairis-Garcia; Cesar Augusto Pospissil Garbossa (Livestock Science, 2026)

Personality or temperament? The answer depends on animal settings and on moral considerations - Isadora de Castro Travnik; Aline Cristina Sant’Anna; Karynn Vieira Capilé; Laura Vitória Fontoura de Lara; Cesar Augusto Taconeli; Carla Forte Maiolino Molento (Journal of Veterinary Behavior, 2026)

Cost-Effective rhamnolipids production from corn Bran and their application in essential oil extraction - Juliana P. Marques Teixeira; Gabriela Dornelas Marques; Michel Pedro Batista; Karen Stefany Conceição; Thaísa Maria da Roda Lino; Natalia Belebecha Terezo; Cesar Augusto Tischer; Alexandre Orsato; Gerson Nakazato; Nicole Caldas Pan; Josiane A. Vignoli; Doumit Camilios-Neto (World Journal of Microbiology and Biotechnology, 2026)

High-resolution site characterization tools: application of fluorescence techniques to identify DNAPL in tropical lands - Lélia Cristina da Rocha Soares; Gabriela Paupitz Mendes; Alexandre Muselli Barbosa; Carlos Cesar Malta-Oliveira; Sandro Souto de Souto; Nestor Kenji Yoshikawa; Claudio Augusto Oller do Nascimento (Chemosphere, 2025)

Photoactivity of Pluronic® F-127 nanoencapsulated hypericin against Leishmania: A promising approach for cutaneous leishmaniasis - Larissa Ferreira de Oliveira; Alanis Boer dos Reis; Ana Paula Rizzo Bueno; Tiffany Suzawa; Maria Julia Schiavon Gonçalves; Anibal Salinas Junior; Ana Carolina Vieira de Oliveira; Paulo Cesar Souza Pereira; Wilker Caetano; Flavio Augusto Vicente Seixas; Áquila Carolina Fernandes Herculano Ramos-Milaré; Daniele Stefanie Sara Lopes Lera-Nonose; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

A new Phanerothecium (Monopisthocotyla, Oogyrodactylidae) species parasitizing Hypostomus strigaticeps (Siluriformes, Loricariidae) in the Pardo River, Southeastern Brazil - Rafael Augusto Pereira da Silva; Julio Cesar Cenci de Aguiar; Mariana Bertholdi Ebert; Reinaldo José da Silva (Systematic Parasitology, 2025)

Rheological Properties and Process Temperature Prediction for the Hot Melt Extrusion of Artesunate with Soluplus®/Span®20 - Fabio Moyses Lins Dantas; Maria Helena Miguez da Rocha-Leão; Daniel Lins de Sales; André Luís Marcomini; Cesar Augusto Gonçalves Beatrice; Carlos Henrique Scuracchio; Pedro Henrique da Rocha Franco; Alessandra Lifsitch Viçosa (AAPS PharmSciTech, 2025)

Alginate-pectin microparticles embedding self-assembling antimicrobial peptides and resveratrol for antimicrobial and anti-inflammatory applications - Cesar Augusto Roque-Borda; Marco Roberto Chávez-Morán; Laura Maria Duran Gleriani Primo; José C.E. Márquez Montesinos; Vinicius Martinho Borges Cardoso; Mauro M.S. Saraiva; Caroline Maria Marcos; Marlus Chorilli; Fernando Albericio; Beatriz G. de la Torre; Fernando Rogério Pavan; Andréia Bagliotti Meneguin (Food Hydrocolloids, 2025)

Development, growth, and flower production of cut sunflower under tropical, subtropical, and temperate environments - Regina Tomiozzo; Lilian Osmari Uhlmann; Leosane Cristina Bosco; Márkilla Zunete Beckmann-Cavalcante; Petterson Baptista da Luz; José Carlos Sorgato; Simone Novaes Reis; Lívia Mendes de Carvalho; Anelise Tessari Perboni; Luana Moraes da Luz; Heberte Fernandes de Figueredo; Sebastião Marcos Silva Valentim; et al. (Horticulture, Environment, and Biotechnology, 2025)

Stabilization of Dispersive Soil Using Calcium Lignosulfonate: Strength, Durability, and Microstructure Assessment - Lisandra Rocha de Moraes; Nilo Cesar Consoli; Cezar Augusto Burkert Bastos (Geotechnical and Geological Engineering, 2025)

Gene expression analysis and halting of ethylene receptors signaling pinpoint ethylene as a positive regulator of direct somatic embryogenesis in Coffea arabica - Natalia Gomes Vieira; Cesar Augusto Nascimento; Ilse Fernanda Ferrari; Mariana Silva Sartorello; Juliana Costa de Rezende; Daniela de Argollo Marques; Angelo Pedro Jacomino; Julieta Andrea Silva de Almeida; Jorge Maurício Costa Mondego (Planta, 2025)

Effects of zinc oxide and monoglyceride blend on intestinal immune, health and microbiota responses of weanling pigs - Ana Lígia Braga Mezzina; Erick Marlon Pereira; Cecília Archangelo Ferreira de Melo; Thallysson Taumaturgo Silva Souza; Matheus Saliba Monteiro; André Pegoraro Poor; Bruno Bracco Donatelli Muro; Caroline Veloso; Flávio de Aguiar Coelho; Rafaella Fernandes Carnevale; Francisco Alves Pereira; Fernanda Mariane dos Santos; et al. (Veterinary Research Communications, 2025)

Effects of climate change and El Niño anomalies on historical declines, extinctions, and disease emergence in Brazilian amphibians - Lucas Ferrante; Fabricio Beggiato Baccaro; Igor Luis Kaefer; Luisa Maria Diele‐Viegas; Augusto Getirana; Celio Fernando Baptista Haddad; Luis Cesar Schiesari; Philip Martin Fearnside (Conservation Biology, 2025)
Amphibian declines, linked to climate change and disease, pose a global challenge, yet their primary drivers remain debated. We investigated the historical decline of Brazilian amphibians by assessing the influence of climate change, extreme weather events, and the chytrid fungus Batrachochytrium dendrobatidis (Bd). Our analysis encompassed 90 amphibian species over more than a century (1900–2014). We integrated historical climate data—including El Niño anomalies and Southern Hemisphere temperature records—with documented extreme weather events and amphibian population trends. We used Granger causality tests to assess the potential of various factors to forecast anuran population declines and extinctions in Brazil and structural equation models to evaluate the relationships between the variables of interest. We identified gradual climate change and extreme weather events, particularly El Niño‐driven temperature anomalies, as the primary drivers of amphibian population declines in Brazil. The structural equation models supported these findings and showed that climate‐driven stressors significantly contribute to population crashes and increase Bd infections. However, Bd infections peaked years after population declines, suggesting that the fungus acts as an opportunistic pathogen rather than a primary driver of amphibian losses in Brazil. These findings challenge the prevailing view that Bd is the main cause of declines, instead highlighting climate anomalies and extreme weather events as the predominant factors.

Ecotoxicological assessment of polycyclic aromatic hydrocarbons and fish biomarkers in a marine protected area - André Vieira Kuhn; João Henrique Alliprandini da Costa; Ursulla Pereira Souza; Gislaine Vanessa de Lima; Pedro Henrique Cipresso Pereira; Rafael Garrett Dolatto; Caio Rodrigues Nobre; Marco Tadeu Grassi; Augusto Cesar; Giorgi Dal Pont; Antônio Ostrensky; Camilo Dias Seabra Pereira; et al. (Regional Studies in Marine Science, 2025)

Evaluation of web post-buckling in high-strength cellular steel and high-strength concrete composite beams: A numerical study - Jonas Yoshihiro Namba; Igor Eduardo da Silva Ribeiro; Haron Cesar Almeida Tavares; Alexandre Rossi; Pablo Augusto Krahl; Carlos Alberto Benedetty Torres; Carlos Humberto Martins (Engineering Structures, 2025)

Using complex diets post-weaning improves piglet performance and financial outcomes - Heng Li Kao Junior; Laya Kannan Silva Alves; Bruno Braga Carnino; Fernanda Mariane dos Santos; Ana Clara Rodrigues de Oliveira; Nádia de Almeida Ciriaco Gomes; Rafaella Fernandes Carnevale; Bruno Bracco Donatelli Muro; Monique Danielle Pairis-Garcia; Allan Paul Schinckel; Cesar Augusto Pospissil Garbossa (Tropical Animal Health and Production, 2025)

Behaviour and welfare of pigeons (Columba livia) in two different localities of Florianópolis, Santa Catarina, Brazil - Eduardo Henrique Gonçalves; Roberta de Farias; Julia Doria de Oliveira Franco; Cesar Augusto Taconeli; Carla Forte Maiolino Molento (Applied Animal Behaviour Science, 2025)

Recent advances and perspectives of eco-efficient building materials from iron ore tailing: characterization, performance, and consumption - Luis Felipe dos Santos Lara; Gustavo Filemon Costa Lima; Laís Resende; Augusto Cesar da Silva Bezerra (Journal of Cleaner Production, 2025)

Regulation of the Caribbean red snapper fishery on the Amazon continental shelf: 60 years of conflict between conservation and exploitation - Alex Garcia Cavalleiro de Macedo Klautau; Rafael Anaisce das Chagas; Paulo Emílio Costa Santos; Bruno Barbosa Iespa; Israel Hidenburgo Aniceto Cintra; Ana Patricia Barros Cordeiro; Wagner Cesar Rosa dos Santos; Jose Augusto Negreiros Aragão; Carlos Eduardo Matos Carvalho Bastos; Flávio de Almeida Alves-Junior; Beatrice Padovani Ferreira; Bianca Bentes da Silva (Marine Policy, 2025)

Comparison of reference evapotranspiration estimates by several models in the region of Western São Paulo Plateau (Brazil) - Maurício Bruno Prado da Silva; Valter Cesar de Souza; Caroline Pires Cremasco; Marcus Vinícius Contes Calça; Cícero Manoel dos Santos; Camila Pires Cremasco; Luís Roberto Almeida Gabriel Filho; Sergio Augusto Rodrigues; João Francisco Escobedo (Arabian Journal of Geosciences, 2025)

A global soil spectral grid based on space sensing - José A.M. Demattê; Rodnei Rizzo; Nícolas Augusto Rosin; Raul Roberto Poppiel; Jean Jesus Macedo Novais; Merilyn Taynara Accorsi Amorim; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Bruno dos Anjos Bartsch; Letícia Guadagnin Vogel; Budiman Minasny; Sabine Grunwald; et al. (Science of The Total Environment, 2025)

A case study on the cost-benefit perspective on the influence of high-protein Distiller's Dried Grains with Solubles (HP-DDGS) pricing and inclusion levels on economic sustainability in pig production - Pollyana Leite Matioli Garbossa; Mirele Daiana Poleti; Cesar Augusto Pospissil Garbossa; Laya Kannan Silva Alves; Rhuan Filipe Chaves; Vinícius de Souza Cantarelli; José Bento Sterman Ferraz (Livestock Science, 2025)

Hymenaea courbaril L. (Fabaceae) seedlings maintain growth but weaken their stem under experimental flooding conditions - Jane Rodrigues da Silva; Fernanda Polli Pinheiro; Alexandre Guillon Valdez Monteiro; Augusto Cesar de Aquino Ribas; Zildamara dos Reis Holsback; Edna Scremin-Dias (Flora, 2025)

Can environmental variables, high sampling density and machine learning deliver detailed maps of soil organic carbon and carbon stock in tropical regions? - Fernanda Almeida Bócoli; Diego Ribeiro; Marcelo Mancini; Leonardo Augusto de Sousa; Samara Martins Barbosa; Milson Evaldo Serafim; Bruno Montoani Silva; Junior Cesar Avanzi; Luiz Roberto Guimarães Guilherme; Nilton Curi; Sérgio Henrique Godinho Silva (CATENA, 2025)

Physicochemical properties, short chain fatty acids production and in vitro fermentation of fibrous ingredients using cecal inoculum from sows - Bruno Bracco Donatelli Muro; Rafaella Fernandes Carnevale; Felipe Norberto Alves Ferreira; Clarice Speridião Silva Neta; Francisco Alves Pereira; Rafaela Scalise Xavier de Freitas; Danny Alexsander Rojas Moreno; Diego Feitosa Leal; Matheus Saliba Monteiro; Ives Cláudio da Silva Bueno; Caio Abércio da Silva; Cesar Augusto Pospissil Garbossa (Animal Feed Science and Technology, 2025)

Impact of high-protein distiller's dried grains with solubles (HP-DDGS) on early growth benefits and carcass quality trade-offs in pigs - Pollyana Leite Matioli Garbossa; Mirele Daiana Poleti; Cesar Augusto Pospissil Garbossa; Laya Kannan Silva Alves; Rhuan Filipe Chaves; Vinícius de Souza Cantarelli; José Bento Sterman Ferraz (Livestock Science, 2025)

Multiplatform Path-ComDim study of Capixaba, indigenous and non-indigenous Amazonian Canephora coffees - Michel Rocha Baqueta; Douglas N. Rutledge; Enrique Anastácio Alves; Manuela Mandrone; Ferruccio Poli; Aline Coqueiro; Augusto Cesar Costa-Santos; Ana Paula Rebellato; Gisele Marcondes Luz; Bruno Henrique Fermino Goulart; Eduardo Jorge Pilau; Juliana Azevedo Lima Pallone; et al. (Food Chemistry, 2025)

Controlling of the Mechanical Behavior of Mass-Stabilized Organic Clay with Various Binders - Victor Núñez; Andres Lotero; Cezar Augusto Bastos; Nilo Cesar Consoli (Geotechnical and Geological Engineering, 2025)

Exposure to microplastics contaminated with pharmaceuticals and personal care products: Histological effects on Ucides cordatus - Letícia Fernanda da Silva; Caio Rodrigues Nobre; Beatriz Barbosa Moreno; Camilo Dias Seabra Pereira; Alexandre Rodrigo Nascimento Gonçalves; Nathalia Sales Soares do Nascimento; Gabriela Pustiglione Marinsek; Renata de Britto Mari; Fábio Ruiz Simões; José Hérelis Carnaúba; Rodrigo Brasil Choueri; Paloma Kachel Gusso-Choueri; et al. (Science of The Total Environment, 2024)

Genetic diversity of Tn916 transposon and its association with tetracycline resistance in Staphylococcus aureus isolates - Hengameh Feyzbakhsh Markhali; Hadi Habibollahi; Mohammad Reza Safari Motlagh; Behzad Kaviani; Cesar Augusto Roque-Borda (Ecological Genetics and Genomics, 2024)

Nanofiber-boosted retrograded starch/pectin microparticles for targeted 5-Aminosalicylic acid delivery in inflammatory bowel disease: In vitro and in vivo non-toxicity evaluation - Andréia Bagliotti Meneguin; Cesar Augusto Roque-Borda; Ana Beatriz Grotto Piperas; Maria Fernanda Ortolani Pollini; Vinicius Martinho Borges Cardoso; Laura Maria Duran Gleriani Primo; Forogh Alemi; Fernando Rogério Pavan; Marlus Chorilli (Carbohydrate Polymers, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Monitoring invasive exotic grass species in ecological restoration areas of the Brazilian savanna using UAV images - Marcos Vinicius Rezende de Ataíde; Silvia Barbosa Rodrigues; Tamilis Rocha Silva; Augusto Cesar Silva Coelho; Ana Wiederhecker; Daniel Luis Mascia Vieira (Remote Sensing Applications: Society and Environment, 2024)

Degradation systems of ferruginous duricrust in the Barreiras Formation, Southeastern Brazil - Ramon Messias Martins; Angélica Fortes Drummond Chicarino Varajão; Fábio Soares de Oliveira; Thierry Allard; Cesar Augusto Chicarino Varajão; Caroline Delpupo Souza (CATENA, 2024)

Challenges, improvements, and opportunities market with the liberalization of the residential electricity market - Virginia Thomasi; Julio Cezar M. Siluk; Paula D. Rigo; Cesar Augusto de O. Pappis (Energy Policy, 2024)

Ten years of directing seeding restoration in the Brazilian savanna: Lessons learned and the way forward - Ana Wiederhecker; Maxmiller Cardoso Ferreira; Silvia Barbosa Rodrigues; Alexandre Bonesso Sampaio; Isabel Belloni Schmidt; José Felipe Ribeiro; Roberto Shojirou Ogata; Maísa Isabela Rodrigues; Augusto Cesar Silva-Coelho; Icaro Sousa Abreu; Thaís Franco Montenegro; Daniel Luis Mascia Vieira (Journal of Environmental Management, 2024)

Nitrogen fertilization in biomass sorghum improves the yield and quality of soybeans grains grown in succession in long-term management systems - Gustavo Ferreira da Silva; Juliano Carlos Calonego; Bruno Cesar Ottoboni Luperini; Larissa Chamma; Willian Aparecido Leoti Zanetti; Emerson Borghi; Rafael Augusto da Costa Parrella; Fernando Ferrari Putti (European Journal of Agronomy, 2024)

A methodology for phase characterization in pellet feed using digital microscopy and deep learning - Thalita Dias Pinheiro Caldas; Karen Soares Augusto; Julio Cesar Alvarez Iglesias; Bernardo Amaral Pascarelli Ferreira; Richard Bryan Magalhães Santos; Sidnei Paciornik; Alei Leite Alcantara Domingues (Minerals Engineering, 2024)

Digestion of whey peptide induces antioxidant and anti-inflammatory bioactivity on glial cells: Sequences identification and structural activity analysis - Fabiana Galland; Juliana Santos de Espindola; Eduarda Spagnol Sacilotto; Lilian Gabriely V.C. Almeida; Joseane Morari; Lício Augusto Velloso; Lucilene Delazari dos Santos; Bruno Cesar Rossini; Maria Teresa Bertoldo Pacheco (Food Research International, 2024)

Present and future distribution of endangered and economically important Ocotea species in the Brazilian Atlantic Forest: Implications for conservation and restoration - Gabriela dos Santos Alves; Alexandre Siminski; Amanda Köche Marcon; Cesar Augusto Marchioro (Forest Ecology and Management, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Assessing the Impact of Climate Change on Argyrotaenia sphaleropa (Meyrick, 1909) Voltinism: Implications for Fruit Production in Southern Brazil - Hevellyn Talissa dos Santos; Cesar Augusto Marchioro (Neotropical Entomology, 2024)

Isoflavone profile and soybean quality: Effects of genotype, cultivation environment and storage - Lázaro da Costa Corrêa Cañizares; Silvia Leticia Rivero Meza; Newiton da Silva Timm; Cesar Augusto Gaioso; Kassiana Kehl; Jessica Fernanda Hoffmann; Cristiano Dietrich Ferreira; Maurício de Oliveira (Biocatalysis and Agricultural Biotechnology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Cotyledons as the primary source of carbon and mineral nutrients during early growth of a savanna tree - Tayara Colins Nunes; Cristiane Silva Ferreira; Thomas Christopher Rhys Williams; Augusto Cesar Franco (Theoretical and Experimental Plant Physiology, 2024)

Evaluation of tourist carrying capacity to support recreational beaches management - Lorrana Lopes Diniz; Phillipe Mota Machado; Adriane Baudson do Nascimento; Leonardo Lopes Costa; Igor David da Costa; Cesar Augusto Marcelino Mendes Cordeiro; Ilana Rosental Zalmon (Ocean & Coastal Management, 2024)

Biallelic variants in GTF3C5, a regulator of RNA polymerase III-mediated transcription, cause a multisystem developmental disorder - Aiko Iwata-Otsubo; Cara M. Skraban; Atsunori Yoshimura; Toyonori Sakata; Cesar Augusto P. Alves; Sarah K. Fiordaliso; Yukiko Kuroda; Jaime Vengoechea; Angela Grochowsky; Paige Ernste; Lauren Lulis; Addie Nesbitt; et al. (Human Genetics, 2024)

In silico toxicologic profile and in vivo trypanocidal activity of estafietin, a sesquiterpene lactone isolated from Stevia alpina Griseb. - Orlando G. Elso; Natacha Cerny; Laura C. Laurella; Augusto E. Bivona; Andrés Sánchez Alberti; Celina Morales; Cesar A. N. Catalán; Emilio L. Malchiodi; Valeria P. Sülsen (Natural Product Research, 2024)

Strategies to extend the shelf life of sheep and goat cheese whey under refrigeration: Nisin, bioprotective culture, and acidification - Fabio Ribeiro dos Santos; Cesar Melo Martins Filho; Rafael F.L. de Cerqueira; Rickey Y. Yada; Pedro Esteves Duarte Augusto; Bruno Ricardo de Castro Leite Junior; Alline Artigiani Lima Tribst (Food Bioscience, 2024)

Empowerment of genetic information by women at-risk of being carriers of Duchenne and Becker muscular dystrophies - Alice Maria Luderitz Hoefel; Cesar Augusto Weschenfelder; Bruna Faria Rosa; Karina Carvalho Donis; Jonas Alex Morales Saute (Journal of Community Genetics, 2024)

Water security threats and solutions in the Grande River basin – One of the Brazilian agricultural frontiers - Alexandre Lima de F. Teixeira; Anik Bhaduri; Cesar Augusto Crovador Siefert; Md Sayed Iftekhar; Stuart E. Bunn; Saulo Aires de Souza; Marco Vinicius Castro Gonçalves; Larissa Corteletti da Costa (Science of The Total Environment, 2024)

Antimicrobial peptides grafted onto the surface of N-acetylcysteine-chitosan nanoparticles can revitalize drugs against clinical isolates of Mycobacterium tuberculosis - Laura Maria Duran Gleriani Primo; Cesar Augusto Roque-Borda; Christian Shleider Carnero Canales; Icaro Putinhon Caruso; Isabella Ottenio de Lourenço; Vitória Maria Medalha Colturato; Rafael Miguel Sábio; Fernando Alves de Melo; Eduardo Festozo Vicente; Marlus Chorilli; Hernane da Silva Barud; Paula Aboud Barbugli; et al. (Carbohydrate Polymers, 2024)

Sand subfractions by proximal and satellite sensing: Optimizing agricultural expansion in tropical sandy soils - Luis Augusto Di Loreto Di Raimo; Eduardo G. Couto; Raul R. Poppiel; Danilo Cesar de Mello; Ricardo S.S. Amorim; Gilmar Nunes Torres; Edwaldo D. Bocuti; Gustavo Vieira Veloso; Elpídio Inácio Fernandes-Filho; Márcio Rocha Francelino; José A.M. Demattê (CATENA, 2024)

Reconstructing the biological invasion of Tuta absoluta: evidence of niche shift and its consequences for invasion risk assessment - Cesar Augusto Marchioro; Flavia Silva Krechemer (Journal of Pest Science, 2024)

Biotic interactions under risk: climate change drives spatial mismatch between a critically endangered tree and its seed dispersers and predators - Cesar Augusto Marchioro; Flavia da Silva Krechemer; Karine Louise dos Santos; Alexandre Siminski (Climatic Change, 2023)

Influence of spontaneous and inoculated fermentation of açai on simulated digestion, antioxidant capacity and cytotoxic activity - Amanda Lais Alves Almeida Nascimento; Mariane Sampaio da Silveira de Souza; Larissa Lorrane Rodrigues Borges; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Adriana Correa Mendonça; Luciana Azevedo; Mariana Araújo Vieira do Carmo; Amanda dos Santos Lima; Laura da Silva Cruz; Gabriel Abranches Dias Castro; Sergio Antonio Fernandes; et al. (Food Research International, 2023)

Lithological control on the formation of ferruginous duricrusts in the Espinhaço Range (Minas Gerais, Brazil) - Alcione Rodrigues Milagres; Fábio Soares Oliveira; Angélica Fortes Drumond Chicarino Varajão; Cesar Augusto Chicarino Varajão; Edgar Batista de Medeiros; Erick Raymond Ramanaidou (CATENA, 2023)

Effect of study area extent on the potential distribution of Species: A case study with models for Raoiella indica Hirst (Acari: Tenuipalpidae) - George Amaro; Elisangela Gomes Fidelis; Ricardo Siqueira da Silva; Cesar Augusto Marchioro (Ecological Modelling, 2023)

Decomposition and nutrient release of green manure biomass in a passion fruit orchard in the brazilian semiarid region - Edilândia Farias Dantas; Ana Dolores Santiago de Freitas; Carolina Etienne de Rosáliae Silva Santos; Augusto Cesar de Arruda Santana; Jéssica Rafaella de Sousa Oliveira; Barbara Laine Ribeiro da Silva; Rosemberg de Vasconcelos Bezerra; Everardo Valadares de Sá Barretto Sampaio (Environmental Monitoring and Assessment, 2023)

Isoflavone profile identification and storage stability of different soybean genotypes sown at standard and late dates in a subtropical climate - Lázaro da Costa Corrêa Cañizares; Newiton da Silva Timm; Cesar Augusto Gaioso; Silvia Leticia Rivero Meza; Jessica Fernanda Hoffmann; Cristiano Dietrich Ferreira; Maurício de Oliveira (Biocatalysis and Agricultural Biotechnology, 2023)

Spatial multicriteria analysis to select suitable sites for sewage sludge use in agriculture: a case study in southeast Brazil - Lucas Almeida Chamhum-Silva; Thiago Bressani-Ribeiro; Lariza Santos Azevedo; Antonio Teixeira Matos; Carlos Augusto Lemos Chernicharo; Cesar Rossas Mota Filho (Environment, Development and Sustainability, 2023)

hCG versus histrelin acetate: ovulation inducing agents in mares (Equus caballus) in a commercial breeding program in Uruguay - Nicolás Cazales; Florencia Pereyra; Sthefanía Icatt; Natalia Jorge Colmán; Cesar Augusto Camacho; María José Estradé; Rodrigo Costa Mattos (Journal of Equine Veterinary Science, 2023)

Radiological assessment of the disposal of bulk oil NORM waste: Case study from Brazil - Amanda Gomes Lopes; Francisco Cesar Augusto Da Silva; Ricardo Tadeu Lopes (Journal of Environmental Radioactivity, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Biochar influences the cane fields’ microbiota and the development of pre-sprouted sugarcane seedlings - Bruna Cristina Pinto; Adriana Barboza Alves; Osania Emerenciano Ferreira; Gustavo Henrique Gravatim Costa; Magno André de Oliveira; Augusto Cesar da Silva Bezerra; Alan Rodrigues Teixeira Machado (Waste Disposal & Sustainable Energy, 2023)

Set of sustainability indicators for the dairy industry - Alexandre André Feil; Caroline Constantin do Amaral; Erica Walter; Cesar Augusto Bagatini; Dusan Schreiber; Alisson Eduardo Maehler (Environmental Science and Pollution Research, 2023)

The 1800-1770 Ma Colider silicic large igneous province in the Amazonian craton: crustal evolution using zircon in situ REE compositions, U-Pb ages and Hf isotope analyses - Bruna Saar Almeida; Carlos Augusto Sommer; Farid Chemale; Antonio João Paes de Barros; Mauro Cesar Geraldes (International Geology Review, 2023)

Perspective: Scientific gaps on forest fires in Brazilian protected areas - Fernanda Moura Fonseca Lucas; Emmanoella Costa Guaraná Araujo; Nilton Cesar Fiedler; José Augusto da Silva Santana; Alexandre França Tetto (Forest Ecology and Management, 2023)

Neuropsychological profile of patients with infectious disease: characterization and comparison of patients with HIV, HTLV, and HCV - Maria Rita Polo Gascón; Giovana S. de Oliveira; Paulo Guirro Laurence; Carolina Fernandes Gualqui; Augusto Cesar Penalva de Oliveira; Jerusa Smid; Luiz A. M. Fonseca; Jorge Casseb; Elizeu Coutinho Macedo (Journal of NeuroVirology, 2023)

PI3Kγ controls IL-17A expression and attenuates alveolar bone loss in an experimental periodontitis model - Marcelo Franchin; Thaise Mayumi Taira; Douglas da Silva Prado; Cesar Augusto Speck Hernandez; Fabio Bonifácio de Andrade; Henrique Ballassini Abdalla; Marcelo Henrique Napimoga; Thiago Mattar Cunha; Sandra Yasuyo Fukada; Pedro Luiz Rosalen (Inflammation Research, 2023)

Antibacterial activity of biosynthesized silver nanoparticles (AgNps) against Pectobacterium carotovorum - Mayra Eleonora Beltrán Pineda; Luz Marina Lizarazo Forero; Cesar Augusto Sierra Avila (Brazilian Journal of Microbiology, 2022)

EPB excavation in transitional mixed face: Line 5—Lilac (São Paulo Metro, Brazil) - Luís Cesar Esteves Flamínio Filho; Marcos Eduardo Hartwig; Cesar Augusto Moreira (Bulletin of Engineering Geology and the Environment, 2022)

A review on some properties of alkali-activated materials - Sâmara França; Marcos Vinicio de Moura Solar Silva; Paulo Henrique Ribeiro Borges; Augusto Cesar da Silva Bezerra (Innovative Infrastructure Solutions, 2022)

Editor’s Highlight: Adaptive responses of tropical savanna trees to frost - Augusto Cesar Franco; Juan Carlos Álvarez‐Yépiz (Trees, 2022)

Correction to: Genetic and Clinical Predictors of Ataxia in Pediatric Primary Mitochondrial Disorders - Juan Sebastian Martin‑Saavedra; Sara Reis Teixeira; Cesar Augusto Pinheiro Ferreira Alves; Fabrício Guimarães Gonçalves; Luis Octavio Tierradentro‑Garcia; Martin Kidd; Colleen Muraresku; ·Amy Goldstein; Arastoo Vossough (The Cerebellum, 2022)

Genetic and Clinical Predictors of Ataxia in Pediatric Primary Mitochondrial Disorders - Juan Sebastian Martin-Saavedra; Sara Reis Teixeira; Cesar Augusto Pinheiro Ferreira Alves; Fabrício Guimarães Gonçalves; Luis Octavio Tierradentro-García; Martin Kidd; Colleen Muraresku; Amy Goldstein; Arastoo Vossough (The Cerebellum, 2022)

Do six-year-old Eucalyptus clones maintain uniformity in growth and wood quality in different soils? - Debora Porfiria Furtado de Lima Maidana; Jane Rodrigues da Silva; Augusto Cesar de Aquino Ribas; Edna Scremin-Dias (Plant and Soil, 2022)

Probabilistic landslide risk assessment in water supply basins: La Liboriana River Basin (Salgar-Colombia) - Cesar Augusto Hidalgo; Johnny Alexander Vega (Natural Hazards, 2021)

Phosphites for the management of anthracnose in soybean pods - Manoel Batista da Silva Junior; Mário Lucio Vilela de Resende; Edson Ampelio Pozza; Alexandre Ribeiro Resende; Victor Augusto Maia Vasconcelos; Ana Cristina Andrade Monteiro; Gustavo Cesar Dias Silveira; Deila Magna dos Santos Botelho (Journal of Plant Pathology, 2021)

Spatio-temporal variation in voltinism of insect pests: sensitivity to location and temperature anomalies - Cesar Augusto Marchioro; Fábio Sampaio; Flavia da Silva Krechemer (Neotropical Entomology, 2021)

Brazilian stingless bees are threatened by habitat conversion and climate change - Valdeir Pereira Lima; Cesar Augusto Marchioro (Regional Environmental Change, 2021)

Auramine dyes induce toxic effects to aquatic organisms from different trophic levels: an application of predicted non-effect concentration (PNEC) - Carina Cristina de Jesus Azevedo; Rhaul de Oliveira; Paula Suares-Rocha; Diego Sousa-Moura; Augusto Tianwen Li; Cesar Koppe Grisolia; Gisela de Aragão Umbuzeiro; Cassiana Carolina Montagner (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Suspension training vs. traditional resistance training: effects on muscle mass, strength and functional performance in older adults - Samuel Domingos Soligon; Deivid Gomes da Silva; João Guilherme Almeida Bergamasco; Vitor Angleri; Ricardo Alessandro Medalha Júnior; Nathalia Fernanda Dias; Sanmy Rocha Nóbrega; Marcelo de Castro Cesar; Cleiton Augusto Libardi (European Journal of Applied Physiology, 2020)

Major mutations in the NS3 gene region of hepatitis C virus related to the resistance to direct acting antiviral drugs: a systematic review - Ana Elisa de Figueiredo Miranda Mundim; Fernanda de Oliveira Feitosa de de Castro; Marina Brandão Braz Albuquerque; Cesar Augusto Sam Tiago Vilanova-Costa; Irmtraut Araci Hoffmann Pfrimer; Antonio Márcio Teodoro Cordeiro Silva (VirusDisease, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

Rhamnolipid production by Pseudomonas aeruginosa grown on membranes of bacterial cellulose supplemented with corn bran water extract - Karen Stefany Conceição; Mayara de Alencar Almeida; Isadora Caroline Sawoniuk; Gabriela Dornelas Marques; Paula Cristina de Sousa Faria-Tischer; Cesar Augusto Tischer; Josiane Alessandra Vignoli; Doumit Camilios-Neto (Environmental Science and Pollution Research, 2020)

Temporal variability of throughfall as a function of the canopy development stage: from seasonal to intra-event scale - José Bandeira Brasil; Eunice Maia de Andrade; Helba Araújo de Queiroz Palácio; Julio Cesar Neves dos Santos; Pedro Henrique Augusto Medeiros (Hydrological Sciences Journal, 2020)

The Biophysical Controls of Macroalgal Growth on Subtropical Reefs - Cesar Augusto Marcelino Mendes Cordeiro; Alastair R. Harborne; Carlos Eduardo Leite Ferreira (Frontiers in Marine Science, 2020)

Root exudate supplemented inoculant of Azospirillum brasilense Ab-V5 is more effective in enhancing rhizosphere colonization and growth of maize - Mayara Silva Barbosa; Elisete Pains Rodrigues; Renata Stolf-Moreira; Cesar Augusto Tischer; André Luiz Martinez de Oliveira (Environmental Sustainability, 2020)

Reintroduction of songbirds from captivity: the case of the Great-billed Seed-finch (Sporophila maximiliani) in Brazil - Ricardo Bomfim Machado; Luís Fábio Silveira; Maria Izabel Soares Gomes da Silva; Flávio Kulaif Ubaid; Cesar Augusto Medolago; Mercival Roberto Francisco; José Carmine Dianese (Biodiversity and Conservation, 2020)

Shoreline Retraction and the Opening of a New Inlet: Implications on Estuarine Processes - Eduardo Siegle; Mariana Afonso Abade Couceiro; Silvia Helena de Mello e Sousa; Rubens Cesar Lopes Figueira; Carlos Augusto França Schettini (Estuaries and Coasts, 2019)

Reducing the water cost in livestock with adoption of best practices - Julio Cesar Pascale Palhares; Esther R. Afonso; Augusto H. Gameiro (Environment, Development and Sustainability, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Structural Quality of an Oxisol Under Conventional Soil Tillage and Predecessor Crops in Sugarcane Rotation - Eber Augusto Ferreira Do Prado; Antonio Carlos Tadeu Vitorino; Rodrigo Arroyo Garcia; Cesar Jose da Silva; Munir Mauad (Sugar Tech, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Population Structure and Genetic Diversity of Common Bean Accessions from Brazil - Giseli Valentini; Maria Celeste Gonçalves-Vidigal; Julio Cesar Ferreira Elias; Leonel Domingos Moiana; Noimilto Nicolau Augusto Mindo (Plant Molecular Biology Reporter, 2018)

Atlantic butterflies: a data set of fruit‐feeding butterfly communities from the Atlantic forests - Jessie Pereira dos Santos; André Victor Lucci Freitas; Keith Spalding Brown; Junia Yasmin Oliveira Carreira; Patrícia Eyng Gueratto; Augusto Henrique Batista Rosa; Giselle Martins Lourenço; Gustavo Mattos Accacio; Márcio Uehara‐Prado; Cristiano Agra Iserhard; Aline Richter; Karine Gawlinski; et al. (Ecology, 2018)
Butterflies are one of the best‐known insect groups, and they have been the subject of numerous studies in ecology and evolution, especially in the tropics. Much attention has been given to the fruit‐feeding butterfly guild in biodiversity conservation studies, due to the relative ease with which taxa may be identified and specimens sampled using bait traps. However, there remain many uncertainties about the macroecological and biogeographical patterns of butterflies in tropical ecosystems. In the present study, we gathered information about fruit‐feeding butterfly species in local communities from the Atlantic Forests of South America. The ATLANTIC BUTTERFLIES data set, which is part of ATLANTIC SERIES data papers, results from a compilation of 145 unpublished inventories and 64 other references, including articles, theses, and book chapters published from 1949 to 2018. In total, the data set contains 7,062 records (presence) of 279 species of fruit‐feeding butterflies identified with taxonomic certainty, from 122 study locations. The Satyrini is the tribe with highest number of species (45%) and records (30%), followed by Brassolini, with 13% of species and 12.5% of records. The 10 most common species correspond to 14.2% of all records. This data set represents a major effort to compile inventories of fruit‐feeding butterfly communities, filling a knowledge gap about the diversity and distribution of these butterflies in the Atlantic Forest. We hope that the present data set can provide guidelines for future studies and planning of new inventories of fruit‐feeding butterflies in this biome. The information presented here also has potential use in studies across a great variety of spatial scales, from local and landscape levels to macroecological research and biogeographical research. We expect that such studies be very important for the better implementation of conservation initiatives, and for understanding the multiple ecological processes that involve fruit‐feeding butterflies as biological indicators. No copyright restrictions apply to the use of this data set. Please cite this Data paper when using the current data in publications or teaching events.

Soybean Yield Gap in the Areas of Yield Contest in Brazil - Rafael Battisti; Paulo Cesar Sentelhas; João Augusto Lopes Pascoalino; Henry Sako; João Paulo de Sá Dantas; Milton Ferreira Moraes (International Journal of Plant Production, 2018)

Screening effects of metsulfuron-methyl to collembolans and earthworms: the role of adjuvant addition on ecotoxicity - Fernanda Benedet de Santo; Guilherme Alves Ramos; Altair Maçaneiro Ricardo Filho; Cesar Augusto Marchioro; Júlia Carina Niemeyer (Environmental Science and Pollution Research, 2018)

Bioprospection of Culturable Endophytic Fungi Associated with the Ornamental Plant Pachystachys lutea - Amanda da Silva Ribeiro; Julio Cesar Polonio; Alessandra Tenório Costa; Caroline Menicoze dos Santos; Sandro Augusto Rhoden; João Lúcio Azevedo; João Alencar Pamphile (Current Microbiology, 2018)

Hydrophysical Quality of an Oxisol Under a No-tillage System with Alternative Crops to Renew a Sugarcane Field - Eber Augusto Ferreira Do Prado; Antonio Carlos Tadeu Vitorino; Rodrigo Arroyo Garcia; Cesar Jose da Silva (Sugar Tech, 2018)

Influence of long-term nutrient manipulation on specific leaf area and leaf nutrient concentrations in savanna woody species of contrasting leaf phenologies - Marina Corrêa Scalon; Mundayatan Haridasan; Augusto Cesar Franco (Plant and Soil, 2017)

N-acylhydrazones containing thiophene nucleus: a new anticancer class - Laura N. F. Cardoso; Thais C. M. Nogueira; Felipe A. R. Rodrigues; Augusto Cesar Aragão Oliveira; Maria Claudia dos Santos Luciano; Claudia Pessoa; Marcus V. N. de Souza (Medicinal Chemistry Research, 2017)

Influence of the Amazon Hydrological Regime on Eutrophication Indicators of a Hydroelectric Power Plant Reservoir - Jean Carlos A. Freire; Rachel Ann Hauser-Davis; Tarcísio da Costa Lobato; Jefferson M. de Morais; Terezinha F. de Oliveira; Augusto Cesar F. Saraiva (Bulletin of Environmental Contamination and Toxicology, 2017)

Submergence, seed germination, and seedling development of the Amazonian floodplain tree Pseudobombax munguba: evidence for root oxytropism - Cristiane Silva Ferreira; Maria Teresa Fernandez Piedade; Augusto Cesar Franco (Trees, 2017)

Expanding our understanding of leaf functional syndromes in savanna systems: the role of plant growth form - Davi Rodrigo Rossatto; Augusto Cesar Franco (Oecologia, 2017)

Effect of Rainfall Characteristics on Runoff and Water Erosion for Different Land Uses in a Tropical Semiarid Region - Julio Cesar Neves dos Santos; Eunice Maia de Andrade; Pedro Henrique Augusto Medeiros; Maria João Simas Guerreiro; Helba Araújo de Queiroz Palácio (Water Resources Management, 2017)

Analytical evaluation of the protection offered by sealed tractor cabins during crop pulverization with fenitrothion - Michelle Barcellos; Milena Michele Faletti; Luiz Augusto dos Santos Madureira; Fernando Cesar Bauer (Environmental Monitoring and Assessment, 2016)

Identification of DNA Methyltransferase Genes in Human Pathogenic Bacteria by Comparative Genomics - Aniel Jessica Leticia Brambila-Tapia; Augusto Cesar Poot-Hernández; Ernesto Perez-Rueda; Katya Rodríguez-Vázquez (Indian Journal of Microbiology, 2016)

Correlation of Metabolic Variables with the Number of ORFs in Human Pathogenic and Phylogenetically Related Non- or Less-Pathogenic Bacteria - Aniel Jessica Leticia Brambila-Tapia; Augusto Cesar Poot-Hernández; Jose Fernando Garcia-Guevara; Katya Rodríguez-Vázquez (Current Microbiology, 2016)

Leaf morphophysiology of a Neotropical mistletoe is shaped by seasonal patterns of host leaf phenology - Marina Corrêa Scalon; Davi Rodrigo Rossatto; Fabricius Maia Chaves Bicalho Domingos; Augusto Cesar Franco (Oecologia, 2016)

Estimating patterns of species biodiversity and behavior of bathyal communities in relation to water dynamics - Delgado Francisco; Basalo Augusto; Pola Cesar; Rodenas Cristina (Frontiers in Marine Science, 2016)

Insights into the distribution and ecology of Hexanchus Griseus in the Cantabrian Sea (NE Atlantic) - Rodríguez-Cabello Cristina; Rodríguez Augusto; Delgado Francisco; González-pola Cesar (Frontiers in Marine Science, 2016)

ASR5 is involved in the regulation of miRNA expression in rice - Lauro Bücker Neto; Rafael Augusto Arenhart; Luiz Felipe Valter de Oliveira; Júlio Cesar de Lima; Maria Helena Bodanese-Zanettini; Rogerio Margis; Márcia Margis-Pinheiro (Plant Cell Reports, 2015)

MDR1 and Cytochrome P450 Gene-Expression Profiles as Markers of Chemosensitivity in Human Chronic Myelogenous Leukemia Cells Treated with Cisplatin and Ru(III) Metallocomplexes - Cesar Augusto Sam Tiago Vilanova-Costa; Hellen Karine Paes Porto; Lucas Carlos Gomes Pereira; Bruno Pereira Carvalho; Wagner Batista dos Santos; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2015)

Starch levels on performance, milk composition and energy balance of lactating dairy cows - Carolina Almeida Carmo; Fernanda Batistel; Jonas de Souza; Junio Cesar Martinez; Paulo Correa; Alexandre Mendonça Pedroso; Flávio Augusto Portela Santos (Tropical Animal Health and Production, 2015)

A Critical Comparison of Different Approaches to Sediment-Quality Assessments in the Santos Estuarine System in Brazil - Ronaldo J. Torres; Augusto Cesar; Victor A. Pastor; Camilo D. S. Pereira; Rodrigo B. Choueri; Fernando S. Cortez; Rodofley D. Morais; Denis M. S. Abessa; Marcos R. L. do Nascimento; Cassia R. Morais; Pedro S. Fadini; Tomas A. Del Valls Casillas; et al. (Archives of Environmental Contamination and Toxicology, 2015)

Genotoxicity and cytotoxicity induced by municipal effluent in multiple organs of Wistar rats - Victor Hugo Pereira da Silva; Carolina Foot Gomes de Moura; Flavia Andressa Pidone Ribeiro; Augusto Cesar; Camilo Dias Seabra Pereira; Marcelo Jose Dias Silva; Wagner Vilegas; Daniel Araki Ribeiro (Environmental Science and Pollution Research, 2014)

The ruthenium complexes cis-(dichloro)tetramineruthenium(III) chloride and cis-tetraammine(oxalato)ruthenium(III) dithionate overcome resistance inducing apoptosis on human lung carcinoma cells (A549) - Cesar Augusto Sam Tiago Vilanova-Costa; Hellen Karine Paes Porto; Flávia de Castro Pereira; Aliny Pereira de Lima; Wagner Batista dos Santos; Elisângela de Paula Silveira-Lacerda (BioMetals, 2014)

Cerrado vegetation and global change: the role of functional types, resource availability and disturbance in regulating plant community responses to rising CO2 levels and climate warming - Augusto Cesar Franco; Davi Rodrigo Rossatto; Lucas de Carvalho Ramos Silva; Cristiane da Silva Ferreira (Theoretical and Experimental Plant Physiology, 2014)

Ouabain-Induced Alterations of the Apical Junctional Complex Involve α1 and β1 Na,K-ATPase Downregulation and ERK1/2 Activation Independent of Caveolae in Colorectal Cancer Cells - Waldemir Fernandes de Souza; Leandro Augusto Barbosa; Lijun Liu; Wallace Martins de Araujo; Julio Cesar Madureira de-Freitas-Junior; Natalia Fortunato-Miranda; Carlos Frederico Leite Fontes; José Andrés Morgado-Díaz (The Journal of Membrane Biology, 2014)

Induction of Cell Cycle Arrest and Apoptosis by Ruthenium Complex cis-(Dichloro)tetramineruthenium(III) Chloride in Human Lung Carcinoma Cells A549 - Aliny Pereira de Lima; Flávia de Castro Pereira; Cesar Augusto Sam Tiago Vilanova-Costa; Jordana Ribeiro Soares; Lucas Carlos Gomes Pereira; Hellen Karine Paes Porto; Luiz Alfredo Pavanin; Wagner Batista dos Santos; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2012)

The ruthenium complex cis-(dichloro)tetrammineruthenium(III) chloride induces apoptosis and damages DNA in murine sarcoma 180 cells - Aliny Pereira de Lima; Flavia de Castro Pereira; Cesar Augusto Sam Tiago Vilanova-Costa; Alessandra de Santana Braga Barbosa Ribeiro; Luiz Alfredo Pavanin; Wagner Batista Dos Santos; Elisângela de Paula Silveira-Lacerda (Journal of Biosciences, 2010)

The Ruthenium Complex cis-(Dichloro)tetraammineruthenium(III) Chloride Presents Selective Cytotoxicity Against Murine B Cell Lymphoma (A-20), Murine Ascitic Sarcoma 180 (S-180), Human Breast Adenocarcinoma (SK-BR-3), and Human T Cell Leukemia (Jurkat) Tumor Cell Lines - Elisângela de Paula Silveira-Lacerda; Cesar Augusto Sam Tiago Vilanova-Costa; Amélia Hamaguchi; Luiz Alfredo Pavanin; Luiz Ricardo Goulart; Maria Inês Homsi-Brandenburgo; Wagner Batista dos Santos; Andreimar Martins Soares; Auro Nomizo (Biological Trace Element Research, 2010)

Producing time series of river water height by means of satellite radar altimetry—a comparative study - Emmanuel Roux; Joecila Santos da Silva; Augusto Cesar Vieira Getirana; Marie-Paule Bonnet; Stéphane Calmant; Jean-Michel Martinez; Frédérique Seyler (Hydrological Sciences Journal, 2010)

The Ruthenium Complex cis-(Dichloro)Tetraammineruthenium(III) Chloride Presents Immune Stimulatory Activity on Human Peripheral Blood Mononuclear Cells - Elisângela de Paula Silveira-Lacerda; Cesar Augusto Sam Tiago Vilanova-Costa; Flávia de Castro Pereira; Amélia Hamaguchi; Luiz Alfredo Pavanin; Luiz Ricardo Goulart; Maria Inês Homsi-Brandenburgo; Andreimar Martins Soares; Wagner Batista dos Santos; Auro Nomizo (Biological Trace Element Research, 2010)

Heart failure increases atrogin-1 and MuRF1 gene expression in skeletal muscle with fiber type-specific atrophy - Robson Francisco Carvalho; Eduardo Paulino Castan; Cesar Augusto Coelho; Francis Silva Lopes; Fernanda Losi Alves Almeida; Aline Michelin; Rodrigo Wagner Alves de Souza; João Pessoa Araújo; Antonio Carlos Cicogna; Maeli Dal Pai-Silva (Journal of Molecular Histology, 2010)

Mutagenic and Genotoxic Effects of cis-(Dichloro)tetraammineruthenium(III) Chloride on Human Peripheral Blood Lymphocytes - Alessandra de Santana Braga Barbosa Ribeiro; Cláudio Carlos da Silva; Flávia de Castro Pereira; Aliny Pereira de Lima; Cesar Augusto Sam Tiago Vilanova-Costa; Simone Santos Aguiar; Luiz Alfredo Pavanin; Aparecido Divino da Cruz; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2009)

Cytotoxic and Genotoxic Effects of cis-Tetraammine(oxalato)Ruthenium(III) Dithionate on the Root Meristem Cells of Allium cepa - Flávia de Castro Pereira; Cesar Augusto Sam Tiago Vilanova-Costa; Aliny Pereira de Lima; Alessandra de Santana Braga Barbosa Ribeiro; Hugo Delleon da Silva; Luiz Alfredo Pavanin; Elisângela de Paula Silveira-Lacerda (Biological Trace Element Research, 2009)

The presence and spectrum of light influences the in vitro conidia production of Mycosphaerella fijiensis causal agent of black Sigatoka - Leonardo Sepúlveda; Luz Estella Vásquez; Clara Inés Paniagua; Dalia Echeverry; Cesar Augusto Hernández; Esperanza Rodríguez; Luis Fernando Restrepo; Rafael Arango (Australasian Plant Pathology, 2009)

Inhibition of cathepsin B by Au(I) complexes: a kinetic and computational study - Shamila S. Gunatilleke; Cesar Augusto F. de Oliveira; J. Andrew McCammon; Amy M. Barrios (JBIC Journal of Biological Inorganic Chemistry, 2008)

Toxicological characterisation of the aqueous soluble phase of the Prestige fuel-oil using the sea-urchin embryo bioassay - Nuria Fernández; Augusto Cesar; Maria José Salamanca; Tomás Ángel DelValls (Ecotoxicology, 2006)